Estrategias de optimización del sistema de control de inventarios en empresas camaroneras del Ecuador - Leon Campos, Madellyne Patricia (2025)
The optimization of inventory control through automatic feeders in the modern business context contributes to the efficiency, profitability, and sustainability of shrimp farming companies, improving inventory control in Ecuador’s shrimp sector. This research focuses on the implementation of automatic feeders as a technological solution. The methodology included a mixed approach, combining qualitative and quantitative analyses, with a descriptive-exploratory design to evaluate current practices and explore new strategies. The automatic feeders enabled precise and controlled feeding, optimizing food usage, reducing waste, and improving shrimp growth. Automation also decreased reliance on intensive labor, resulting in greater operational efficiency and a significant reduction in operational costs. The results showed that, although the initial investment in these technologies is high, the return on investment is quick due to increased efficiency and reduced waste. Furthermore, this innovation contributed to the environmental sustainability of the sector by reducing its carbon footprint and reinforcing its commitment to sustainable production.